Optimalisasi Penulisan Karya Tulis Ilmiah untuk Peningkatan Jenjang Karier Guru Madrasah Ibtidaiyah - syihaabul Hudaa; Mustofa Fahmi; Zulfikah Nur; Mafrudah Mafrudah (Jurnal Elementaria Edukasia, 2023)
The problem teachers face in MI in scientific writing is the need for more understanding of writing correct articles. The introductory text in journals often includes a theoretical foundation, so many articles are rejected. In addition, the need for more understanding of OJS makes teachers often submit manuscripts with the help of others. The purpose of this article is to present the research results conducted by researchers with respondents of teachers and madrasah heads from all madrasahs in Bogor, West Java. This research belongs to the descriptive qualitative type using a direct action research approach. The data source comes from madrasah teachers, and research data comes from the results of evaluations conducted by researchers. From the research conducted, it is concluded that teachers have sufficient competence in understanding scientific writing, with an average of 79.5. The Ministry of Religious Affairs can optimize teachers' writing skills by conducting FGDs and collaborating across madrasahs with journal managers. Thus teachers can produce output in scientific papers to improve their career path.